BV and non-BV associated Gardnerella vaginalis establish similar synergistic interactions with other BV-associated microorganisms in dual-species biofilms. (December 2015) - Castro, Joana; Cerca, Nuno
Abstract: Dual-species biofilm formation between Gardnerella vaginalis strains isolated from women with or without bacterial vaginosis (BV) and other 24 BV-associated microorganisms support that the key difference in virulence potential between BV-negative and BV-positive G. vaginalis strains seems not to be related with biofilm maturation.